Insulin resistance, autophagy and apoptosis in patients with polycystic ovary syndrome: Association with PI3K signaling pathway - Tong, Cheng; Wu, Yue; Zhang, Lingling; Yu, Ying (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a disease in which endocrine metabolic abnormalities coexist with reproductive system abnormalities, with the main clinical manifestations including abnormal menstruation, hirsutism, acne, infertility, and obesity, and it is also a high risk for the development of many pregnancy complications, gynecological malignancies and other diseases. Therefore, timely intervention to prevent the progression of PCOS is of great significance for improving the quality of life of most female patients. Insulin resistance (IR) is one of the most common endocrine disorders in PCOS patients, with approximately 75% of PCOS patients experiencing varying degrees of IR. It is now believed that it is mainly related to the PI3K signaling pathway. The role of autophagy and apoptosis of ovarian granulosa cells (GCs) in the pathogenesis of PCOS has also been gradually verified in recent years. Coincidentally, it also seems to be associated with the PI3K signaling pathway. Our aim is to review these relevant studies, to explore the association between the IR, cellular autophagy and apoptosis in PCOS patients and the PI3K pathway. We summarize some of the drug studies that have improved PCOS as well. We have also found that proteomics holds great promise in exploring the pathogenesis of PCOS, and we have published our views on this.